Cytoprotective effect of seaweeds with high antioxidant activity from the Peniche coast (Portugal). (1st March 2017) - Pinteus, Susete; Silva, Joana; Alves, Celso; Horta, André; Fino, Nádia; Rodrigues, Ana Inês; Mendes, Susana; Pedrosa, Rui
Highlights: We screened the antioxidant activity of twenty-seven macroalgae from Portugal. We screened the toxicity of the most active algae in MCF-7 cells. Most algae presenting high antioxidant activity exhibited cytoprotective effect. High antioxidant activities may not always display the highest cytoprotective effect. Abstract: Screening of antioxidant potential of dichloromethane and methanolic extracts of twenty-seven seaweeds from the Peniche coast was performed by: total phenolic contents (TPC), 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and oxygen radical absorbance capacity (ORAC). Seaweeds revealing the highest antioxidant activity were screened for cytoprotective potential in MCF-7 cells, including the mitochondrial membrane potential analysis and the caspase-9 activity. High correlation was found between TPC of seaweed extracts and their scavenging capacity on DPPH and peroxyl radicals. The highest antioxidant activity was displayed by the methanolic fraction of brown seaweeds belonging to Fucales, however Ulva compressa presented the highest cytoprotective effect by blunting the apoptosis process. These results suggest that high antioxidant activity may not be directly related with high cytoprotective potential. Thus, seaweeds reveal to be a promising source of compounds with potential against oxidative stress.